Germs are not for sharing / los gérmenes no son para compartir ebook - Verdick, Elizabeth (Best Behavior., 2023)
Germs Are Not for Sharing/Los gérmenes no son para compartir paperback (ages 4–7): Sneezes, coughs, runny noses, spills, and messes are facts of everyday life with young children. This book teaches kids what germs are, what they do, and why it's so important to cover them up, block them from spreading, and wash them down the drain. Includes tips for parents and caregivers. A section for adults reinforces the book's message that crying is a natural, normal response to strong feelings and includes tips and activities in both English and Spanish to help children express and handle their feelings. Best Behavior series Simple words and lively full-color illustrations guide children to choose positive behaviors. Select titles are available in two versions: a durable board book for ages 1–4 and an expanded paperback for ages 4–7. Bilingual board book and paperback editions of all titles also are available. Kids, parents, and teachers love these award-winning books. All include helpful tips for teachers, caregivers, and parents.